PENGARUH KECERDASAN EMOSIONAL (EQ), FASILITAS BELAJAR, TEMAN SEBAYA, DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA DENGAN DISIPLIN BELAJAR SEBAGAI VARIABEL INTERVENING PADA MATA PELAJARAN IPS TERPADU DI SMP NEGERI 1 AMPEK NAGARI - Dewi, Indah Puspita; Eprillison, Vivina; Amaluis, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research results show that: 1) Emotional intelligence has a significant effect on learning discipline. Emotional intelligence influences learning achievement through indirect influence on learning discipline as shown by the path coefficient value of 0.495. 2) Learning facilities have a significant effect on learning discipline. Learning facilities influence learning achievement through indirect influence on learning discipline which is shown to obtain a path coefficient value of 0.116. 3) Peers have a significant influence on learning discipline. Peers influence learning achievement through indirect influence on learning discipline which is shown to obtain a path coefficient value of 0.233. 4) The family environment has a significant effect on learning discipline. The family environment influences learning achievement through indirect influence on learning discipline as shown by the path coefficient value of 0.308. 5) Emotional intelligence has a significant effect on learning achievement. Emotional intelligence influences learning achievement directly as shown by the path coefficient value of 2.089. 6) Learning facilities have a significant effect on learning achievement. Learning facilities directly influence learning achievement as shown by the path coefficient value of 0.635. 7) Peers have a significant influence on learning achievement. Peers influence learning achievement directly, resulting in a path coefficient value of 0.768. 8) The family environment has a significant effect on learning achievement. The family environment directly influences learning achievement as shown by the path coefficient value of 1.099. 9) Learning discipline has a significant effect on learning achievement. Learning discipline influences learning achievement directly as shown by the path coefficient value of 3.861.